2009
DOI: 10.1149/1.3204392
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Vacancy Distributions by Decoration with Hydrogen

Abstract: A well-known method for the determination of vacancy distributions in silicon is based on the decoration of vacancies with in-diffused platinum (Pt) and subsequent profiling of the Ptdistribution with DLTS (Deep Level Transient Spectroscopy) analysis. The vacancy profile can then be correlated with the substitutional Pt profile. However, there are significant drawbacks of this method: The in-diffusion of platinum is a high-temperature step, which already can alter the vacancy profile; moreover, DLTS measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…After implantation, the proton-implanted samples are annealed under inert atmosphere or in air (no difference between the different atmospheres is observed) at 470±10 °C for 5 h or 15 h. The post-implantation hydrogen-plasma exposures are realized with a Radio-Frequency setup operating at 13.56 MHz standard frequency providing a plasma power of 150 W. The plasma hydrogenations are carried out at 450±1 °C for either 15 min or 60 min (see Ref. [18] for more details).…”
Section: Methodsmentioning
confidence: 99%
“…After implantation, the proton-implanted samples are annealed under inert atmosphere or in air (no difference between the different atmospheres is observed) at 470±10 °C for 5 h or 15 h. The post-implantation hydrogen-plasma exposures are realized with a Radio-Frequency setup operating at 13.56 MHz standard frequency providing a plasma power of 150 W. The plasma hydrogenations are carried out at 450±1 °C for either 15 min or 60 min (see Ref. [18] for more details).…”
Section: Methodsmentioning
confidence: 99%
“…The basic core complex evolves from crystal damage induced by the irradiation. Thus, such donor-like defect states may also be observed in samples irradiated with neutrons (5), electrons (6), or helium (7) if the hydrogen necessary for the decoration of the core complexes is provided -e.g., by in-diffusion from a hydrogen plasma source (7)(8)(9)(10). Depending on the temperature of the annealing step, different energy levels with ionization energies of several 10 meV were reported and associated with HDs (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying defect species of the induced shallow donors are intrinsic point defect complexes (probably vacancy or multi-vacancy complexes) which are decorated with hydrogen, where the basic core complex evolves from crystal damage caused by the irradiation. Thus, such donor-like defect states may also be observed in samples irradiated with neutrons (5), electrons (6) or helium (7) if the hydrogen necessary for the decoration of the core complexes is provided -e. g., by indiffusion from a hydrogen plasma source (7)(8)(9)(10). Depending on the temperature of the annealing step, different energy levels with ionization energies of several 10 meV were reported and associated with the hydrogen-decorated intrinsic defect donor species (HDs) (5,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…During the successive annealing step, the implanted hydrogen diffuses through the silicon layer penetrated by the implantation and, depending on the annealing conditions, the donor profile may therefore fully develop toward the surface (14). In case of providing the necessary hydrogen by a plasma source at the surface of a float zone silicon sample with radiation damage introduced beforehand by light ion irradiation, it was found that an overexposure with hydrogen led to diminishing effective carrier concentrations in the sample (7)(8)(9)(10). When using proton implantation to create the HDs, the defects and the hydrogen are inserted simultaneously and, in contrast to the in-diffusion of the hydrogen from the plasma, the amount of introduced hydrogen is known and controllable.…”
Section: Introductionmentioning
confidence: 99%